Thin slender concrete rectangular walls in moderate seismic regions with a single reinforcement layer (2020)
Some Latin-American countries, including Colombia, Peru, Panamá and the Dominican Republic, have adopted an industrialized system for the construction of buildings using thin slender reinforced concrete walls. The main advantage of this system is that it can increase the construction speed and reduce the use of nonstructural walls, as all architectonical spaces are defined by the structural walls. Additionally, designers tend to use thin structural walls with low steel reinforcement ratios, which is reflected in a reduction of the construction cost. The typical wall section for 6 to 10-story buildings is characterized by a thickness of around 100 mm and a single layer of welded wire mesh acting as longitudinal and transverse reinforcement. Additional reinforcing bars may be placed at the wall edges to increase moment capacity, but in most cases, there are no confined boundary elements along the edges. Despite the system's popularity, experimental data for these types of walls is still scarse. In addition to this, structural walls of low thickness and high aspect ratio with unconfined or poorly confined boundary elements have shown structural deficiencies in the 2010 Central Valley Chile earthquake. In this paper, existing and new experimental data from representative thin slender walls, used in moderate seismic regions, was analyzed to evaluate the structural system under lateral loads. Two unconfined reinforced concrete walls with typical section detailing were tested. Additionally, these tests were complemented with an experimental database of 28 rectangular wall units of thickness less than 100 mm, as reported in the literature. This data was used to analyze the behavior of rectangular thin slender walls in terms of axial load ratio, boundary elements conditions, plastic hinge length, and maximum drift capacity. The experimental data shows a significant reduction in drift capacity as axial load, clear interstory height to wall thickness ratio, or wall length increases. It is also evident that plasticity is concentrated at the base of the walls, mainly due to the low vertical reinforcement ratios. Finally, a capacity vs. demand stochastic analysis was carried out to evaluate the performance of buildings up to 10 stories in a moderate seismic zone. These analyses show that for moderate seismic regions the probability of reaching a severe damage limit state is low for buildings configured with rectangular walls having a single layer of reinforcement. © 2019 Elsevier Ltd